Qualidade do cuidado à pessoa idosa com diabetes e/ou hipertensão atendida na Atenção Primária à Saúde - Liliam Barbosa Silva (2018)
This study is part of the second stage of the study "Aging and Kidney Disease" (en-DoRen), which aimed to estimate the prevalence of non-dialytic chronic kidney disease (CKD) in older people. The first stage identified a high prevalence of CKD (24.0%) and low awareness of its status (13.9%), with higher percentages of consciousness in the more advanced stages (stages 3-5). These findings made to question the existence of probable inadequacies in the quality of care for the older people with a chronic condition, especially in Primary Health Care (PHC), being a thematic yet little explored in the literature, which justified the study. Objective: To evaluate the quality of care for the older people with diabetes and/or hypertension accompanied by Family Health teams. Methods: This is a study of mixed methods with explanatory sequential design QUANQUAL. Initially, a quantitative study was carried out, with a cross-sectional design (Phase 1), followed by a qualitative research based on the perspective of Social Construcionism (Phase 2). Phase 1 data (QUAN) were collected between August 2014 and January 2017, and involved the 300 older people participants of the first stage of the en-DoRen study, residing in one of the nine health districts of Belo Horizonte, Minas Gerais. A household survey was conducted and a semi-structured questionnaire was used, containing sociodemographic, behavioral and clinical information. The Patient Assessment of Chronic Illness Care (PACIC) questionnaire was also used to assess the quality of care, and obtained secondary information from the consultation to the electronic health record in PHC. A sample of biological material was still collected for laboratory tests. Phase 2 (QUAL) involved in-depth individual interviews with 20 seniors selected from the previous phase from November to December 2017. The quantitative data were analyzed through descriptive techniques, logistic regression, multiple correspondence analysis and cluster. The qualitative data were analyzed from the discursive practices proposed by Spink. For the organization and analysis of the interviews, the maps were used. The Chronic Care Model (CCM) and the Chronic Conditions Care Model (MACC) were the main theoretical references that supported the discussion of the findings, with emphasis on self-care support and risk stratification, as well as the explanatory models of satisfaction proposed by Atkinson and Medeiros, focusing on culpability. Results: The study sample was characterized by a high prevalence of cardiovascular diseases (24.1%). Among the risk factors were arterial hypertension (83.9%) and dyslipidemia (82.6%), and a higher frequency of simultaneity between 3 and 4 cardiovascular risk factors (CVRF) (51.8%). Approximately, half of the participants were dependent on the public health service (48.8%). After adjusted analysis, female and non-white skin color were associated with the accumulation of CVRF in the private sector, while female and age range 65 to 74 year olds in the public sector. As weaknesses in the conformity of care practice, the evaluation of the diabetic foot and the request for specialized examinations were the most highlighted. Multiple correspondence analysis identified that dimension 1 separates individuals regarding clinical aspects and levels of satisfaction, while dimension 2 contrasts individuals with the worst outcome of care. Regarding the quality of primary care, the median PACIC score was 1.55 (IQ 1.30-2.20), and the "Delivery System Design/Practice Design" dimension presented better scores (2.33; IQ 1.50-3.00). Despite the low quality of chronic care, a high level of user satisfaction was verified, which provoked a qualitative exploration of this contrasting finding. After construction of the maps, the following theme was highlighted: Culpability as a mediator filter: satisfaction processed and transformed. This theme resulted of the problematization of the situations experienced in the PHC services by the older people whose sense of use of interpretive repertoires related to culpability allowed them to express favorably their satisfaction with these health services. The theme was constituted by four subthemes, three representing a type of imputation of culpability made by the older people and the last, expressing the result of these attributions, as a possible reflection of the place that occupies in the current configuration of the public health system. Conclusion: The prevalence of cardiovascular diseases and their modifiable risk factors was high in the older people studied, tending to be more concentrated in individuals with greater social vulnerability in both the public and private sectors. Also, low scores of PACIC and its dimensions were evidenced, indicating that the chronic care according to the CCM in the PHC seems still far from its assumptions. Despite this, the older people tended to express satisfaction for these services, and a possible explanation for this seemingly unjustified satisfaction was the presence of mediator filters, highlighting "culpability". demarcating modern forms of moral regulation through new strategies of socially and historically instituted blame. It is necessary, therefore, to break with the cycle that perpetuates old strategies of moral regulation, which are socially and historically instituted.